Effects of transcutaneous electrical diaphragmatic stimulation on the cardiac autonomic balance in healthy individuals: a randomized clinical trial - Luana Godinho Maynard; André Sales Barreto; Valter Joviniano Santana-Filho; Manoel Luiz de Cerqueira Neto; Daniel Penteado Martins Dias; Walderi Monteiro da Silva-Júnior (Universidade de São Paulo, 2016)
ABSTRACT The transcutaneous electrical diaphragmatic stimulation (TEDS) is a technique of respiratory muscle activation that affects breathing pattern and rhythm. In an attempt to evaluate changes in cardiac autonomic balance in response to TEDS in healthy individuals, we used a well-established TEDS model. Twenty-two volunteers aged between 22 and 35 years old, with no cardiac pathology history, were randomized into two groups (control, n = 8; TEDS, n = 14). The individuals were allowed to rest in supine position and were then subjected to the electrical stimulation protocol. The control group was subjected to electrical stimulation at perceptive level, whereas for the TEDS group the electric stimulus generated diaphragm contraction. Cardiac intervals (CI) were sampled by a Polar RS800CX monitor. Cardiac interval variability was studied in the time and frequency domains. In the control group, electrical stimulation did not change cardiac interval length and variability (CI: 761±44 vs. 807±39 ms; RMSSD: 37±9 vs. 42±13 ms ; LF: 69±6 vs. 67±5 nu; HF: 31±6 vs. 33±5 nu; all comparisons versus baseline). Nevertheless, as compared to baseline, TEDS group showed decreased sympathetic cardiac modulation (LF: 43±3 vs. 63±4 nu) and increased parasympathetic cardiac modulation (RMSSD: 109±10 vs. 41±6 ms; HF: 57±3 vs. 37±4 nu) during diaphragmatic stimulation. However, cardiac interval length was not changed by electrical stimulation (CI: 686±59 vs. 780±31 ms). It can be suggested that the use of TEDS stimulus leads to pronounced changes in the cardiac sympathovagal balance, with higher parasympathetic cardiac modulation, possibly induced by increased diaphragmatic excursion.